Interpretation of the concept of method in Descartes' philosophy - Saeed, Shangar Jabbar Rashid Saeed; Abbas, Asst.Prof.Dr Batool Raza Abbas (Sulaimani Journal for Humanities, 2025)
This study analyses methods in Descartes' philosophy. Descartes used the concept of doubt for his method for the sake of reviewing information and avoiding doubt in order to arrive at true and clear knowledge and wise cleansing of errors dispersion. His doubt is an intellectual scenario that directs thoughts; he utilizes so much doubt until it reaches the truth. This kind of doubt begins with doubt and ends with certainty. In Descartes' view, the method they used was doubt but it was not an absolute doubt, rather a temporary doubt so that they reach certainty. Descartes sets four laws for doubt, which is certainty and true knowledge, following and achieving the truth of these laws are the law of certainty, the law of analysis, the law of draftinginterpretation, the laws of review or statistics. These four laws are derived from the spirit of mathematical science that rejects vague identification. The method that Descartes wants to investigate systematically is that logically everything can be doubted, something that we have always accepted as truth. First, Descartes doubts the senses, the intellect, and the external world, then towards Certainty proceeds on the principle that all perceived doubt must be rejected by thought. When Descartes doubted his existence, he wanted to prove the existence of God. That is to say, the existence of the outside world is the three assurances of the general framework to include the details of Cartesian philosophy that finally became the foundation of modern philosophy. His approach has had a lasting impact on philosophy and scientific method.
Keywords: Descartes; Method; Doubt; Knowledge